Clinical Pharmacology and Therapeutic Applications of Topical Corticosteroids in Contemporary Pharmacy Practice-An Updated Review for Pharmacists - Alazmi, Abdalmjeed Awod; Mabrok Musalm Eid Alazmi; Mohammed Ali Hamzah Albuhaydil; Faisal Abdullah Ahmad Alshlali; Saleh Sarhan M Al Rashedi; Zaki Essa Yosef Alhiri; Khaled Salim Al-Azmi (Saudi Journal of Medicine and Public Health, 2025)
Background: Topical corticosteroids (TCS) are cornerstone therapies in dermatology owing to anti-inflammatory, immunosuppressive, antiproliferative, and vasoconstrictive actions. They are indicated across steroid-responsive dermatoses, with potency, vehicle, site, and duration determining benefit–risk. Aim: To provide pharmacists with an updated, practice-focused review of the clinical pharmacology, therapeutic indications, dosing, safety, and patient counseling considerations for TCS. Methods: Narrative synthesis of regulatory labeling, dermatology guidelines, and key clinical literature on mechanisms, pharmacokinetics, potency classification, administration principles, dosing by fingertip units (FTUs), special populations, adverse effects, contraindications, monitoring, and interprofessional roles. Results: TCS effectively manage psoriasis, eczematous disorders, lichen planus/ simplex, discoid lupus, lichen sclerosus, alopecia areata, phimosis, and radiation dermatitis; selected off-label uses (e.g., scalp psoriasis maintenance; limited evidence in urticaria) may be appropriate with oversight. Pharmacokinetics are driven by percutaneous absorption (affected by vehicle, site thickness, inflammation, occlusion). Seven potency classes guide selection; once- or twice-daily application suffices. FTU-based dosing standardizes quantity. Risks include local atrophy, striae, perioral dermatitis, tachyphylaxis, and rare systemic HPA suppression—heightened in children, older adults, thin or damaged skin, high potency, large areas, or occlusion. Absolute contraindications include untreated bacterial infections. Conclusion: Rational agent/vehicle selection, limited duration, site-appropriate potency, FTU dosing, and vigilant monitoring optimize outcomes and minimize harms. Pharmacists are pivotal in education, adherence support, and safety surveilla nce.